Application of Organic Fertilizer in Sidenuk Varieties to Reduce Using Urea - Nurrobifahmi, Nurrobifahmi; Flatian, Anggi Nico; Bachtiar, Taufiq; Citraresmini, Ania; Hanani, Muftia; Slamet, Sudono (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2021)
Sidenuk rice is a superior rice variety produced by BATAN through a radiation mutation technique. The new varieties that have been produced need to be supported by efforts to optimize production through fertilization technology. The purpose of this study was to determine the effect of organic fertilizer which can increase growth, production and reduce the use of urea fertilizer in lowland rice optimally. The study was conducted using a completely randomized design. Each was repeated 4 times so that the total experimental unit (pot) was 32 rice pots. The treatments include (1) Control (without urea fertilizer), (2) Control (+) 100% urea, (3) 50% urea, (4) Local microorganisms (MOL), (5) Compost, (6) Biochar , (7) Azolla, (8) Mol + Compost + Biochar + Azola + SP 36 and KCl. The results showed that the highest grain weight was found in the 100% urea treatment, which was 43.97 g plant-1. MKBA treatment (MOL fertilizer, compost, biochar, azolla) showed values that were not significantly different from 100% urea treatment. Organic fertilizer formula (MOL fertilizer, compost, biochar, azolla) can reduce the use of urea fertilizer by 50%.